Body and testicular development and serum testosterone concentrations in Brahman males - Chacur, Marcelo George Mungai; Arikawa, Alex Miyasaki; Oba, Eunice [UNESP]; Souza, Camila Dutra; Gabriel Filho, Luis Roberto Almeida [UNESP] (Universidade Estadual de Londrina, 2017)
The present study had the objective of evaluating the physical and testicular development, and the serum testosterone concentration of 8 to 18 months old male Brahman cattle on grazing weight gaining performance tests. Bovine cattle (n=40), aged 259.76 ± 26.15 days and weighing 239.71 ± 33,94kg had the following characteristics evaluated every 56 days, corresponding to 8, 10, 12, 14, 16, and 18 months of age (six different data collections): body weight (BW), scrotal circumference (SC), girth (G), height at the withers (WH), body length (BL), body mass index (BMI), right and left testicular length (RTL and LTL, respectively), right and left testicular height (RTH and LTH, respectively), average daily weight gain (ADG), testicular volume (TV), and serum testosterone (ST).Analysis of variance and Tukey's test at 5% probability were used. Correlations between variables were assessed using Pearson's method at 5% confidence. There was significant difference (P < 0.05) from 12 months of age onwards for ADG and ST. There were differences (P < 0.05) for: BW, SC, G, WH, BL, BMI, RTL, LTL, RTH,and TV from 14 months of age. There was a positive correlation between: ST x G (r=0.38; P < 0.01); ST x WH (r=0.38; P < 0.01); ST xRTH (r=0.23; P < 0.05); ST x LTH (r=0.21; P < 0.01); ST x TV (r=0.22; P < 0.008); TV x weight (r=0.70; P < 0.01); TV x SC (r=0.90; P < 0.01); and TV x BMI (r=0.93; P < 0.01). A rapid increase in serum testosterone concentration occurred between 12 and 14 months of age, followed by rapid body and testicular growth. An elevation in testosterone levels is an indirect indicator that an acceleration inphysical and testicular growth is approaching. It is recommended to calculate both BMI and TV to follow cattle growth due to the high correlation between these variables.
Keywords: Androgen; Body morphometry; Male zebu; Testes